Identification of Pesticide Prophenophos and Chlorantraniliprole Indigenous Degrading Bacteria in Jombang East Java - Pratiwi, Wardha Maulidya; Asri, Mahanani Tri (LenteraBio : Berkala Ilmiah Biologi, 2022)
The use of pesticides with the active ingredients of prophenophos and chlorantraniliprole on agricultural land in Jombang, which is not controlled either in dose or frequency, can cause physical, chemical, and biological soil damage. One way to repair is by utilizing bacteria indigenous. The purpose of this study was to isolate and identify a bacterium exposed to the pesticide prophenophos and chlorantraniliprole in agricultural land, Jombang, East Java. This type of research is an observational study and analyzed descriptively. The procedure for isolation and propagation of bacteria by the method streak plate in media nutrient agar. Identification was carried out on macroscopic and microscopic morphological characters while for biochemical characters with Microbact Identification System Kit GNB 24E. The isolated bacteria were then identified using microbact software and Bergey's Manual of Determinative Bacteriology Ninth Edition. This study obtained the results in the form of three bacterial isolates that were isolated and identified as Bacillus stearothermophilus, Bacillus badius, and Bacillus alvei with the results of the percentage accuracy of similarity coefficients of 70%, 70%, and 60%. The three isolates of bacteria indigenous that have been identified can be used as bioremediation agents on agricultural soil contaminated with the pesticides prophenophos and chlorantraniliprole.